EFFECTS OF CYANIDE ON ORNAMENTAL CORAL FISH (CHROMIS VIRIDIS) - Arifin, Zainal; Hindarti, Dwi (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2006)
The use of cyanide particularly for fishing has caused concern for its impacts on aquatic marine life. This study was the first attempt to provide information on the effect of cyanide on tropical marine fish in Indonesia and aimed to determine the toxicity of cyanide to coral fish, Chromis viridis. The fish were exposed to 10,18,32,56 and 100 µg 1-1 of cyanide. These five cyanide concentrations were tested for 96- h period of exposure through a static-renewal. Cyanide was found to be very toxic to the fish. The 96-h LC50 of cyanide for juvenile of Chromis viridis was 41.3 µg 1-1. The toxicity of cyanide to C. viridis was 300 times stronger than that of the trace metal cadmium. Compared to milkfish fry (Chanos chanos), C. viridis was more sensitive to cyanide. It is estimated that at concentration of 32 µg 1-1 cyanide does not show observable effect (NOEC) to C. viridis. Meanwhile the lowest observable effect of cyanide (LOEC) to the fish is at a concentration of 56 µg 1-1.